Antibacterial Potential Chloroform Extract of Photobacterium phosphoreum Bacteria Symbiotic in Light Organs of Squid Loligo duvauceli - Iin Putriyani; Delianis Pringgenies; Ali Ridlo (Jurnal Moluska Indonesia, 2020)
Microorganisms that live in association with marine invertebrates are able to produce a compound similar  to those produced by marine invertebrates and are thought to be potential as bioactive materials. Supplement  extracts from the Photobacterium phosphoreum bacterial culture have been shown to have antibacterial activity. The purpose of this study was to determine the anti-bacterial activity of the chloroform extract of Photobacterium  phosphoreum biomass against pathogenic bacteria Bacillus substilis, Staphylococcus aureus, Salmonella sp. and  Escherichia coli. The extraction process was carried out by the liquid-liquid extraction method. Fractionation was  performed using Open Column Chromatography (KKT). The antibacterial activity test was conducted by the agar diffusion method according to Kirby-Bauer. The results showed that for the antibacterial activity test of crude  extract, the largest inhibition zone diameter occurred in Escherichia coli with a concentration of 50 µg / disk at 24 h incubation, namely (9.80 ± 0.75 mm), while the smallest inhibition zone diameter occurred in Salmonella sp. by  giving a concentration of 10 µg / disk at an incubation time of 48 hours, namely (6.03 ± 0.05) mm. Of the 6  fractions resulting from crude extract fractionation, it was known that fraction 5 was the most active fraction and  inhibited the growth of the tested bacteria. The largest inhibition zone diameter occurred in Escherichia coli (9.83  ± 0.28) mm, while the smallest inhibition zone diameter occurred in Salmonella sp. (8.63 ± 0.20 mm)